Altered Sense of Body Ownership and Agency in Posttraumatic Stress Disorder and Its Dissociative Subtype: A Rubber Hand Illusion Study - Rabellino, Daniela; Burin, Dalila; Harricharan, Sherain; Lloyd, Chantelle; Frewen, Paul A.; McKinnon, Margaret C.; Lanius, Ruth A. (Frontiers in Human Neuroscience, 2018)
Traumatic experiences have been linked to the development of altered states of consciousness affecting bodily perception, including alterations in body ownership and sense of agency, the conscious experience of the body as one’s own and under voluntary control. Severe psychological trauma and prolonged distress may lead to posttraumatic stress disorder (PTSD).Together, symptoms of derealization and related specifically to the sense of body ownership and agency, of depersonalization (where parts of the body or the entire body itself is perceived as detached and out of control), constitute the dissociative subtype (PTSD+DS). In this study, we explored the Rubber Hand Illusion, an experimental paradigm utilized to manipulate sense of body ownership in PTSD (n=4) and PTSD+DS (n=6) as compared to healthy controls (n=7). Perceived finger location and self-report questionnaires were used as behavioral and subjective measures of the illusion, respectively. In addition, the correlation between the illusion’s effect and sense of agency as a continuous feeling of controlling one’s own body movements was explored. Here, a lower illusion effect was observed in the PTSD as compared to the control group after synchronous stimulation for both the proprioceptive drift and subjectively perceived illusion. Moreover, by both proprioceptive drift and by subjective ratings, the PTSD+DS group showed a response characterized by high variance, ranging from a very strong to a very weak effect of the illusion. Finally, sense of agency showed a trend towards a negative correlation with the strength of the illusion as subjectively perceived by participants with PTSD and PTSD+DS. These findings suggest individuals with PTSD may, at times, maintain a rigid representation of the body as an avoidance strategy, with top-down cognitive processes weakening the impact of manipulation of body ownership. By contrast, the response elicited in PTSD+DS appeared to be driven by either an increased vulnerability to manipulation of embodiment or a dominant top-down cognitive representation of the body, with disruption of multisensory integration processes in both cases. Taken together, these findings further our understanding of bodily consciousness in PTSD and its dissociative subtype and highlight the supportive role played by sense of agency for the maintenance of body ownership.